A atuação do diretor na gestão escolar nos centros municipais de educação infantil: um estudo de caso em Francisco Beltrão/PR - Cucchi, Andréia Zuchelli (2019)
This dissertation entitled "The actuation of the director in school management in the Municipal Centers of Childhood Education: A case study in Francisco Beltrão / PR" is a result of research linked to the Research Group: Representations, Spaces, Times and Languages in Educational Experiences - RETLEE , of the Graduate Program in Education - Master's Degree - Area of concentration: Education, Research Line: Culture, educational processes and teacher training, of the State University of the West of Paraná - UNIOESTE / Campus de Francisco Beltrão / PR. The objective of this study is to understand how the directors' activities in school management, developed in the Municipal Centers of Childhoord Education of Francisco Beltrão / PR. The objective of this study is to understand how the directors' activities in school management, developed in the Municipal Centers of Childhood Education of Francisco Beltrão / PR. Its development took place from the understanding of the historical trajectory and the implantation of the first institutions of childhood education, considering the path from the European context to arriving in Brazil, Paraná and Francisco Beltrão. The research aims to address the importance of the initial formation of the school director, opportunized by the Universities. The research methodology is characterized as a case study and were used as instruments for data collection: questionnaires and semi-structured interviews. The research was carried out with 19 directors of CMEIs, 01 (one) former president of the Association of Protection to Maternity and Childhood, 01 (one) collaborator of the Protection Association to Maternity and Childhood, 01 (one) / Department of Childhood Education from February to June 2018. The results show the historical advances of school management in the Municipal Centers of Childhood Education, based on the actution of the director, regarding the attendance of children attending institutions from birth to three (3) years of age, in the valuation of education professionals who work in children's education, in the regulation of the legislation of the process of normalization to choose the function and the process of choice through the election with the participation of the community. As well as, the significant changes in the pedagogical practice of CMEIs and the improvement of the physical structure of educational spaces. In addition to the process of continuous training that contributes to the improvement and qualification of the director for the exercise of the function. This allows for significant improvements in the teaching and learning process and, consequently, the development of children attending CMEIs. The realization of the research corroborates in a direct way in the understanding of the school management of the CMEIs, through the actuation of the director's. It is justified by the need to understand the activities inherent to the pedagogical and administrative practice developed in the institutions of childhood education of the municipality, through the actuation of the teacher of the childhood education in the exercise the function of director in the CMEIs.